Brides and widows: Iconic dress and identity in Howard Barker's costumes. Issue 1 (1st June 2017) - Kipp, Lara Maleen
One of the strongest recurring motifs in the work of contemporary British playwright Howard Barker is women's marital status: brides and widows abound in his work. Their status as such is often crucially configured, but also subverted through their costumes (in a Western cultural context). This article considers the central role that brides and widows play in a variety of Barker's dramatic texts and identifies some core working principles with regard to his use of costume. It explores the notion of the iconic garment, as proposed by Hannah in 2014, and its influence on these characters' identities. Drawing on aesthetic discourse, in particular that of the sublime, I analyse how Barker proposes a reconsideration of stable subject identity through these recognizable, yet ambiguous and unstable female figures.